Effect of Different PH Light Qualities and Some Growth Regulators on Seed Germination of Bidens biternata (Lour.) Merr and Sherff. - Ahlawat, A. S.; Dagar, J. C. (Indian Forester, 1980)
In the present investigation effects of pH, light qualities and some growth regulators on seed germination ofBidens biternata-a medicinal herb of family Asteraceae, have been investigated. At pH 2.5 there was complete inhibition of germination but the germination percentage gradually increased from pH 3 pH 7. Again in the basic medium there was decline and at pH 9 percentage germination was again zero red light prompted seed germination, yellow and continuous lights showed little effect while blue and green lights inhibited. IAA and IPA enhanced germination percentage at lower concentrations ( up to 10 ppm) but the higher concentrations of these substances proved inhibitory, GA3, enhanced germination upto 50 ppm.